IPTEKS PERHITUNGAN RASIO KEUANGAN UNTUK MENILAI KINERJA PT. BANK SULUTGO PERIODE TAHUN 2014 – 2017 - Voerman, Chriseva D. F.; Lambey, Robert (Universitas Sam Ratulangi, 2018)
PT Bank SulutGo is one of the BUMD (Regional-Owned Enterprises) companies that also have a goal to earn profits and aim to maintain a healthy bank predicate. By analyzing financial statements, it can be seen how the condition or financial performance of the bank, in accordance with regulations circulated by Bank Indonesia on April 12, 2004, namely indicators used to measure the soundness of a bank or not by using CAMEL analysis or ratio analysis. To analyze bank financial ratios, divided into three ratios, namely: bank liquidity ratio, bank solvency ratio, and bank profitability ratio. The results of the financial statement banking ratio analysis from 2014 - 2017 PT Bank SulutGo showed good conditions, although the Asset to loan ratio and Assets Utilization were in an unfavorable condition.Keywords: Ratio analysis, financial performance, financial statement